2006
DOI: 10.1002/cmdc.200500095
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of the Kynurenine Pathway of Tryptophan Metabolism: Synthesis and Preliminary Biological Evaluation of (S)‐4‐(Ethylsulfonyl)benzoylalanine, a Potent and Selective Kynurenine Aminotransferase II (KAT II) Inhibitor

Abstract: (S)‐4‐(Ethylsulfonyl)benzoylalanine is a potent and selective inhibitor of kynurenine aminotransferase II (KAT II) with no significant effect on KAT I or other enzymes of the kynurenine pathway. This compound is able to pronouncedly inhibit the formation of kynurenic acid (KYNA) in rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 20 publications
2
70
0
Order By: Relevance
“…From the outset, these agents were not only viewed as tools to study the neurobiology of KYNA, but were also appreciated for their potential therapeutic applications (Schwarcz and Pellicciari, 2002;Varasi et al, 1996). ESBA, which was used in the present study, was introduced as the first specific KAT-II inhibitor in 2006 (Pellicciari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…From the outset, these agents were not only viewed as tools to study the neurobiology of KYNA, but were also appreciated for their potential therapeutic applications (Schwarcz and Pellicciari, 2002;Varasi et al, 1996). ESBA, which was used in the present study, was introduced as the first specific KAT-II inhibitor in 2006 (Pellicciari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological Inhibition of Kynurenine Pathway-(S)-4-(Ethylsulfonyl) benzoylalanine hydrochloride (Enzo Life Sciences) inhibits kynurenine aminotransferase II (KAT-II) (21), and Ro61-8048 (Tocris Bioscience) is a competitive inhibitor of kynurenine 3-hydroxylase (22). 100 mM stock solutions in PBS were prepared for both inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…To test this conjecture, we focused on two enzymes, KAT-II and kynurenine 3-hydroxylase (Kyn-3OH), for which specific inhibitors with proven efficacy in mouse models are available. KAT-II and Kyn-3OH are selectively inhibited by (S)-4-(ethylsulfonyl) benzoylalanine hydrochloride (21) and Ro61-8048 (22), respectively (supplemental Fig. S1A).…”
Section: Ido1mentioning
confidence: 99%
“…[3,14] Recently, we reported the synthesis and biological characterization of (S)-4-ethylsulfonylbenzoylalanine (S-ESBA, 5), the first potent and selective inhibitor of KAT II, which is the dominant KYNA-forming enzyme in the rat brain. [15] Biological assays conducted in vitro showed that S-ESBA (5) inhibits KAT II obtained from partially purified rat liver with an IC 50 value of 6.1 mm. In vivo studies support these results, demonstrating that the administration of S-ESBA (5) lowers the extracellular levels of KYNA in the hippocampus of unanesthetized rats.…”
mentioning
confidence: 99%
“…In vivo studies support these results, demonstrating that the administration of S-ESBA (5) lowers the extracellular levels of KYNA in the hippocampus of unanesthetized rats. [15] Herein we report a novel and more efficient synthesis of S-ESBA (5) and an analysis of its inhibitory activity using purified recombinant human KAT II. The data are discussed in light of the crystal structure of human KAT II in complex with its natural substrate l-Kyn (1), [16,17] and on the basis of conserved and nonconserved residues that feature the sequences of speciesspecific orthologs of KAT II (human, rat, and mouse).…”
mentioning
confidence: 99%